A Miniaturized, Programmable Deep-Brain Stimulator for Group-Housing and Water Maze Use - Pinnell, Richard C.; Pereira de Vasconcelos, Anne; Cassel, Jean C.; Hofmann, Ulrich G. (Frontiers in Neuroscience, 2018)
Pre-clinical deep-brain stimulation research has observed a growing interest in the use of portable stimulation devices that can be carried by animals. Not only can such devices overcome many issues inherent with a cable tether, such as twisting or snagging, they can also be utilized in a greater variety of arenas, including enclosed or large mazes. However, these devices are not inherently designed for water-maze environments, and their use has been restricted to individually-housed rats in order to avoid damage from various social activities such as grooming, playing or fighting. By taking advantage of 3D-printing techniques, this study demonstrates an ultra-small portable stimulator with an environmentally-protective device housing, that is suitable for both social-housing and water-maze environments. The miniature device offers 2 channels of charge-balanced biphasic pulses with a high compliance voltage (12V), a magnetic switch, and a diverse range of programmable stimulus parameters and pulse modes. The device's capabilities have been verified in both chronic pair-housing and water-maze experiments that asses the effects of nucleus reuniens DBS. Theta-burst stimulation delivered during a reference-memory water-maze task (but not before) had induced performance deficits during both the acquisition and probe trials of a reference memory task. The results highlight a successful application of 3D-printing for expanding the range of measurements capable in deep-brain stimulation research.